Correlations between physical and chemical characteristics of Cortibel guava (Psidium guajava L.) fruits grown in the Brazilian Cerrado - Rodrigues Gomes, Francielly; Morais Silveira, Kamilla; Rodrigues Marques, Cláudia Dayane; Ferreira, Beatriz Alves; Lopes Barros, Ângela; Hurtado Salazar, Alejandro; Pereira da Silva, Danielle Fabíola; da Silveira Neto, Américo Nunes (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2023)
The correlation between physical and chemical attributes of fruits can serve as indicators for the ideal harvest time and function as selection criteria to enhance the management and productivity of crops. This study aimed to investigate the correlations among physical and chemical properties of Cortibel guava fruits grown in the Brazilian Cerrado. Parameters assessed included skin and pulp color, weight, diameter, length, total soluble solids, titratable acidity, and the ratio of these characteristics. Data were analyzed using Pearson's linear correlation with a significance level of P < 0.05. Several physical and chemical properties of the fruits exhibited significant correlations. The highest correlation coefficients were observed between weight and fruit diameter, as well as between hue angle of the skin and skin lightness. The properties of Cortibel guava fruits cultivated in the Brazilian Cerrado exhibit significant correlations. These findings enable the utilization of straightforward parameters in the selection processes of Cortibel guava for breeding objectives. Highlights: Guava is a significant crop with high economic value. The characterization of fruits assists in selecting genotypes with desirable commercial properties. Cortibel guava fruits exhibited significant correlations between some physical and chemical characteristics. The correlations between the physical and chemical characteristics of the fruits allow the selection of materials of interest for breeding.